Peningkatan Hasil Belajar Mata Pelajaran Materi Turunan Fungsi Melalui Pembelajaran Langsung (Direct Instruction) - Ariani, Rahayu Septi (Jurnal Pembelajaran Prospektif, 2017)
To improve the students’ learning achievement, Mathematics teachers are demanded to help their students through the use of direct instruction in the teaching process. By implementating direct instruction, the teachers transform lessons directly to the students to solve their learning achievement problem of low yields due to the students’ learning capability in implementing various learning models. Many teachers give assignments to the students without being carefully checked. Feeling saturated in their learning activities, less attention and less accountability, the assignments instructed were not done by them as scientifically expected. Based on the identification of the problem, the researchers intended to resolve the students’ problem on their learning achievement by applying active learning methods; specifically, direct instruction.